Hydroxyapatite Advances in Composite Nanomaterials, Biomedical Applications and Its Technological Facets - Thirumalai, Jagannathan (IntechOpen, 2018)
The goal of this book is to provide readers with a broad appraisal of topics in global advancements in theoretical and experimental facts, and practical applications of nano-HAp materials based on their synthesis, properties, prospects, and potential biomedical treatments. The perspective of this book involves the preparation of crystalline nano-HAP materials including preferential orientation, various properties and new prospects in biomimetics, bone tissue infections, biomedical implants, regenerative medicinal treatments and a wide range of technological applications. This book is categorized into two main sections: Hydroxyapatite: synthesis, properties, perspectives, and prospects; and the application of hydroxyapatite: a synergistic outlook. Individual chapters provide a base for a wide range of readers from diversified fields, including students and researchers, who will find in this book simply explained basics as well as advanced techniques of specific subjects related to these phenomena. The book is made up of nine contributions, compiled by experts from wide-ranging fields involved in biomaterials/materials in science and technology from over 15 research institutes across the globe.